In vitro digestion of protein-based nanohydrogels incorporating curcumin as a lipophilic model compound: effect of a chitosan coating - Pinheiro, A. C. (2016)
[Excerpt] Introduction: One of the challenges of food enrichment with lipophilic bioactive compounds is related with their poor solubility in food matrices and their instability during digestion, leading to a poor bioavailability. These challenges are promoting research efforts to find more effective delivery systems based on natural biopolymers. Protein nanohydrogels can be used as carriers of bioactive compounds in food products, however, during gastric digestion, proteins are denatured by environmental conditions and hydrolyzed by enzymes. One of the strategies to improve protein nanohydrogels’ stability and the controlled release of active ingredients during gastrointestinal (GI) digestion is the addition of a coating (polysaccharide layer). The behavior of lactoferrin (Lf)–glycomacropeptide (GMP) nanohydrogels with and without a chitosan coating was evaluated during GI digestion. [...]